Urban popular place names past and present - Sven Steffens (Brussels Studies, 2007)
Molenbeek-Saint-Jean/Sint-Jans-Molenbeek is a former village on the outskirts of Brussels that underwent a gradual process of urbanisation starting in 1800 that culminated in its becoming an integral part of the capital. In studying the names and nicknames that the residents give to the places where they live, this toponymic study shows us the borough’s life: urbanisation, industrialisation, economic decline, migrations, and changes in language use. The entire history of a region unfurls before our eyes thanks to the perceptions and mentalities that these place names express, complete with the residents’ ambitions and sources of pride, tensions between ethnic groups and social strata, and changes in social realities